Analisis Bisnis Telur Asin dengan Metode SWOT dan Fish bone di UMKM Desa Wonosari - Hurun 'in; Samsudin Bahari (JERA : Journal of Engineering Research and Application, 2024)
Wonosari Village MSMEs are Wonosari MSMEs that produce high quality salted eggs. However, MSME sales are unstable. The problems that occur in the MSMEs NR Wonosari Village district include a few marketing areas, small capital, the quality of eggshells that are easily cracked, problems of low productivity in producing, and difficulties in finding suppliers. The external problems are the lack of guidance and supervision from local governments on the existence of the salted egg industry. Due to the unstable state of MSME sales results, a study was conducted "Salted Egg Business Analysis with SWOT and Fish bone Methods in MSMEs Wonosari Village". Based on the analysis that has been done, it can be known the attributes that are obstacles or problems in MSMEs Salted Egg NR from the Fish bone method, it can be known the obstacles are: limited employees, lack of knowledge, no applicable SOP, less long incubation process, perishable raw materials, difficult to find duck breeders. And by using the SWOT method, it can be known the problem attributes from the threats and weaknesses matrix columns, including: the existence of similar and the same salted egg business, products are easy to imitate, uncertain raw material prices, uncertain quality of raw materials, human resources still lack knowledge, limited raw materials, limited distribution, lack of promotional media. Keywords: Salted Egg MSMEs, SWOT, Fish Bone Method.